Effects of Different Type of 6-weeks Tele-exercise Against Obese Employees Body Composition and Fitness Level during Covid-19 Pandemic - Kuswari, Mury; Rimbawan, Rimbawan; Hardinsyah, Hardinsyah; Dewi, Mira; Gifari, Nazhif (Universitas Negeri Semarang, 2021)
Obesity may cause coronary heart disease, hypertension, stroke, and other cardiovascular illness. Basic national health research on Indonesia (Riskesdas) showed that there is a growing trend on adult obesity: 10.5% in 2007, 14.8% in 2013 and 21.8% in 2018. Obese people are commonly having a low fitness level. In this time of pandemic, tele- exercise, or live exercise via live, online video, may become an effective substitute for exercise outside of home, mainly for employees who spent most of their time in front of a computer. The aim of this study itself is to analyse the effects of basic strength tele-exercise vs. combination of strength and cardio tele-exercise on fitness and body composition. This research was a quantitative, descriptive observational study, with cross-sectional design. Data collection and intervention was taken and given respectively for 3 months. Intervention was given via live online video, using Zoom as a medium, consisting of 3 days of exercise/week. The subjects was then divided into 3 groups: strength exercise (SE), strength-cardio exercise (SC), and control (CT) group. Independent variable is exercise while dependent variables are body composition (fat mass, total body water, fat-free mass, protein mass, mineral mass, and percent body fat and fitness level(VO 2 Max, push-up count, sit-up count, sit-and-reach distance). We found that all aspects of subjects’ body composition (fat mass, total body water, protein mass, mineral mass, percent body fat, fat-free mass) did not significantly change for all groups (pgt;0.05). In SE, there are significant changes in flexibility and cardiorespiratory fitness, while in SC, all aspects of fitness are increased. We suggest that diet must be monitored as well, and timing of body composition and hydration status must be taken into consideration.